ゴク・ロデンシェーラプ著『『般若心〔経〕の広大注』の解説』校訂テクストと訳注 - Horiuchi, Toshio (Bulletin of the International Institute for Buddhist Studies, 2019)
rNgog Blo ldan shes rab’s (1059-1109) Shes rab snying po’i rgya cher ’grel gyi bshad pa (hereafter rNgog) is a kind of sub-commentary on Vimalamitra’s commentary on the Heart Sutra (hereafter HS), named, *Āryaprajñāpāramitāhṛdayaṭīkā (hereafter PHT). In this article, I present a critical edition and annotated Japanese translation of the rNgog. After a careful comparison with the PHT and other texts, this article clarifies the following important points, which were not addressed or were misunderstood in previous studies.